WEB BASED INTERNAL QUALITY MANAGEMENT INFORMATION SYSTEM A DESIGN AND PROTOTYPING - Yato, Dhimas Buing Rindi Widra; Hidayat, Zulham (Scientific Journal of Information System, 2024)
Improving the quality of education in higher education institutions is crucial to support the development of human resources and the progress of the nation. Utpadaka Swastika University, as one of the higher education institutions in Indonesia, is committed to producing high-quality and competitive graduates. To ensure this quality, an effective and efficient internal quality assurance system (SPMI) is necessary. This research aims to design and build an internal quality assurance system based on the web using PHP and MySQL at Utpadaka Swastika University with the prototyping method. Software testing is conducted through Black Box Testing. This internal quality assurance system aims to ensure the quality of higher education provided by universities through the implementation of the Tridharma of Higher Education, in order to realize the vision and meet the needs of stakeholders. The achievement of quality assurance goals through the internal quality assurance system will be accredited through external quality assurance systems. This system can assist in presenting document information accessible to program heads, leaders, auditors, administrators, and quality assurance body (LPM) leaders. It facilitates program heads in the process of collecting and submitting documents for evaluation and audit instruments, allowing the LPM to directly identify issues and quality standards in the internal quality assurance process. This system is expected to be used as a reference for further development of an Internal Quality Assurance System so that the system can have better features.